Enrichment characteristics and biological effects of 133CsCl in black porgy Acanthopagrus schlegelii - Zheng, Caoqun; Liu, Gongye; Shao, Liang; Zeb, Rabia; Wang, Lei; Zhang, Hongmai; Zheng, Ronghui; Fang, Chao; Huang, Youyou; Yu, Tao; Bo, Jun (Frontiers in Marine Science, 2025)
The release of cesium (Cs) isotopes from treated nuclear-contaminated water at Japan’s Fukushima Daiichi Nuclear Power Plant (FDNPP) has raised global concern due to their potential long-term environmental impacts. Some of these isotopes have a physical half-life of 30.17 years, posing a potential threat to marine environments and marine life. This study used the stable isotope 133Cs to simulate exposure and assess the ecological risks associated with Cs isotopes in marine environments. The black porgy (Acanthopagrus schlegelii) was selected as the model organism and was exposed to various concentrations of 133Cs (0.02, 0.2, 2, and 20 mg/L). Although 133Cs exhibited low bioaccumulation in black porgy, it still showed potential for biomagnification. The fish demonstrated a strong stress response and some antioxidant adaptation at 3 days, but significant cellular and tissue damage occurred after 14 days of exposure. Analysis of the Integrated Biomarker Response version 2 (IBRv2) further revealed that the black porgy was more sensitive to Cs at 3 days, with toxic effects intensifying over time. This study provides a scientific basis and experimental reference for assessing the ecological risks of Cs isotopes in marine ecosystems.